Catena-Poly triphenyltin(IV) -mu-2- (3,5-di-tert-butyl-4-hydroxybenzyl) sulfanyl acetato-kappa O-2:O ' - Lee, S.M.; Robinson, W.T.; Ali, Hapipah Mohd; Lo, K.M. (International Union of Crystallography, 2009)
The title compound, [Sn(C6H5)(3)(C17H25O3S)](n), comprises two symmetry-independent five-coordinated triphenyltin molecules which are linked by carboxylate bridges into a polymeric chain. The Sn-IV atom is in a distorted trans-C3SnO2 trigonal-bipyramidal geometry. The presence of two bulky tert-butyl groups on the benzene ring prevents any hydrogen-bonding interactions involving the hydroxyl substituents.